Off-pump Revascularization with Bilateral versus Single Mammary Arteries—A Propensity Score-Matched Analysis - Puehler, Thomas; Zittermann, Armin; Dia, Mohamad; Emmel, Eric; Gercek, Mustafa; Börgermann, Jochen; Hakim-Meibodi, Kavous; Gummert, Jan (The Thoracic and Cardiovascular Surgeon, 2019)
Background Coronary artery bypass grafting is the first-line therapy for severe multivessel coronary artery disease. We aimed to investigate the clinical outcome in patients undergoing isolated off-pump surgery with the single or bilateral internal mammary artery (SIMA or BIMA) approach.Methods We performed a propensity score-matched analysis in 1,852 consecutive patients, aged 50 to 70 years, who underwent myocardial revascularization at our institution between July 2009 and August 2016. Primary end point was the probability of survival.Results Mean follow-up was 36.3 (range: 0.1–89.6) months. The probability of survival in the SIMA and BIMA groups was 98.6 and 99.0% at year 1, 92.0 and 92.5% at year 5, and 85.6 and 81.6% at year 7, respectively, with a hazard ratio (HR) of mortality for the BIMA group versus the SIMA group of 0.98 (95% confidence interval[CI]: 0.64–1.52; p = 0.94). There was evidence for interaction between diabetes and study group on mortality risk (HR = 2.59, 95% CI: 1.07–6.23; p = 0.034). Freedom from mediastinitis/wound infection was higher in the SIMA group than in the BIMA group (99.5 and 96.9%, respectively; HR of an event = 6.39, 95% CI: 2.88–14.18; p < 0.001). The corresponding values in the subgroups of diabetic patients were 98.6 and 90.9%, respectively (HR = 6.45, 95% CI: 2.24–18.58; p = 0.001). Mediastinitis/wound infection was associated with increased mortality risk (HR = 2.96, 95% CI: 1.29–6.78; p = 0.010).Conclusion Overall, our data indicate similar probability of survival up to a maximum follow-up of 7 years by off-pump surgery with the SIMA or BIMA approach. However, in diabetic patients, the clinical outcome indicates caution regarding the use of the BIMA approach.
Keywords: off-pump; cardiac surgery; coronary artery bypass grafting; single internal mammary artery; bilateral internal mammary artery; coronary artery disease; propensity score matching